2017
DOI: 10.13114/mjh.2017.352
|View full text |Cite
|
Sign up to set email alerts
|

Work Stress, Perception of Job Safety, and Job Satisfaction of Rope Access Technicians and the Relationship between Them

Abstract: Work stress, while affecting employee productivity and job satisfaction, is an important factor that causes serious injuries and even death at work. For this reason, to determine and to propose solutions for those factors affecting job stress is essential for dangerous jobs such as rope access technicians. The main purpose of this study was to examine: job stress, job satisfaction and the perception of job safety of rope access technicians and to show if there are any relations between these factors. The parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…Kaplan and Eren (2018) and Wu et al (2018) also found that the perception of occupational health and safety has a negative and significant effect on work stress, and as work stress increases, the safety level is negatively affected. Çetinkaya and Aras (2017) found a positive and significant relationship between occupational safety and work stress in their studies. Korkmaz et al (2018) revealed that as the participants’ occupational safety increased, the tension related to work decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Kaplan and Eren (2018) and Wu et al (2018) also found that the perception of occupational health and safety has a negative and significant effect on work stress, and as work stress increases, the safety level is negatively affected. Çetinkaya and Aras (2017) found a positive and significant relationship between occupational safety and work stress in their studies. Korkmaz et al (2018) revealed that as the participants’ occupational safety increased, the tension related to work decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Dengan demikian, nilai rata-rata sebesear 4,23 menunjukan bahwa secara umum Pegawai Kantor Jasa Raharja di Lampung, Sumsel, Jambi, Riau, Bengkulu, dan Sumut merasakan bahwa hindrance stressors memiliki pengaruh positif dalam dirinya. Banyak peneliti yang menyatakan bahwa hindrance stressors merupakan jenis stress yang sifatnya menghambat pertumbuhan dan pencapaian pribadi serta dapat mengakibatkan kesusahan(Cetinkaya & Aras, 2017;French et al, 2019a;French et al, 2019b;LePine et al, 2022).Berbeda dengan stress yang bersifat tantangan atau challenge stressors, beberapa tuntutan pekerjaan atau keadaan lingkungan kerja menghasilkan stres tanpa disertai adanya perasaan eustress. Sementara stress yang bersifat tantangan atau hindrance stressors ini cenderung diasosiasikan dengan prestasi kerja.…”
unclassified